Scintillation and irregularities from the nightside part of a Sun-aligned polar cap arc - van der Meeren, Christer; Oksavik, Kjellmar; Lorentzen, Dag Arne; Paxton, Larry J.; Clausen, Lasse Boy Novock (Journal of Geophysical Research: Space Physics, 2016)
In this paper we study the presence of irregularities and scintillation in relation to the nightside part of a long-lived, Sun-aligned transpolar arc on 15 January 2015. The arc was observed in DMSP UV and particle data and lasted at least 3 h between 1700 and 2000 UT. The arc was more intense than the main oval during this time. From all-sky imagers on Svalbard we were able to study the evolution of the arc, which drifted slowly westward toward the dusk cell. The intensity of the arc as observed from ground was 10–17 kR in 557.7 nm and 2–3.5 kR in 630.0 nm, i.e., significant emissions in both green and red emission lines. We have used high-resolution raw data from global navigation satellite systems (GNSS) receivers and backscatter from Super Dual Auroral Radar Network (SuperDARN) radars to study irregularities and scintillation in relation to the polar cap arc. Even though the literature has suggested that polar cap arcs are potential sources for irregularities, our results indicate only very weak irregularities. This may be due to the background density in the northward IMF polar cap being too low for significant irregularities to be created. publishedVersion